Promotion of angiogenesis toward transplanted ovaries using nitric oxide releasing nanoparticles in fibrin hydrogel. (29th December 2021) - Yang, Chungmo; Chung, Nanum; Song, Chaeyoung; Youm, Hye Won; Lee, Kangwon; Lee, Jung Ryeol
Abstract: Transplantation of ovary is one method of facilitating fertility preservation to increase the quality of life of cancer survivors. Immediately after transplantation, ovaries are under ischemic conditions owing to a lack of vascular anastomosis between the graft and host tissues. The transplanted ovaries can suffer damage because of lack of oxygen and nutrients, resulting in necrosis and dysfunction. In the technique proposed in this paper, the ovary is encapsulated with nitric oxide-releasing nanoparticles (NO-NPs) in fibrin hydrogels, which form a carrying matrix to prevent ischemic damage and accelerate angiogenesis. The low concentration of NO released from mPEG-PLGA nanoparticles elicits blood vessel formation, which allows transplanted ovaries in the subcutis to recover from the ischemic period. In experiments with mice, the NO-NPs/fibrin hydrogel improved the total number and quality of ovarian follicles after transplantation. The intra-ovarian vascular density was 4.78 folds higher for the NO-NPs/fibrin hydrogel groups compared to that for the nontreated groups. Finally, in vitro fertilization revealed a successful blastocyst formation rate for NO-NPs/fibrin hydrogel coated ovaries. Thus, NO-NPs/fibrin hydrogels can provide an appropriate milieu to promote angiogenesis and be considered as adjuvant surgery materials for fertility preservation.